Bootstrap Statistical Model of Tooth Surface Deviation of Heat Treatment Deformation of Batch Spiral Bevel Gears - Weihao Sun; Jubo Li; Tianxing Li; Chuang Jiang; Songlin Wang; Jianxin Su (Jixie chuandong)
Aiming at the same batch of spiral bevel gears with the same gear material， NC milling method and heat treatment specification， a bootstrap resampling is carried out on a small number of tooth surface deviation sample data based on the bootstrap method， a large number of sample data are obtained and a bootstrap statistical model of batch spiral bevel gear tooth surface deviation is established； the probability characteristic value of the sequential points of tooth surface measurement is calculated， and whether they conform to the normal distribution is tested by k-s； the estimated true value， estimated interval and other parameters are selected to describe their statistical laws and results； through the cubic NURBS surface fitting method， the variation law of the tooth surface deviation of the whole batch is obtained， and the effective evaluation of the tooth surface accuracy of the whole batch is realized. The bootstrap statistical model provides a theoretical basis for guiding the modification of tooth surface processing parameters and efficient and stable production.